Efficacy and Safety of Everolimus With Reduced Tacrolimus in Liver Transplant Recipients: 24-month Results From the Pooled Analysis of 2 Randomized Controlled Trials. Issue 7 (July 2021) - Lee, Sung-Gyu; Jeng, Long-Bin; Saliba, Faouzi; Singh Soin, Arvinder; Lee, Wei-Chen; De Simone, Paolo; Nevens, Frederik; Suh, Kyung-Suk; Fischer, Lutz; Jin Joo, Dong; Fung, John; Joh, Jae-Won; et al.
Abstract : Background and Methods: Data from 2 randomized liver transplant trials (N = 772; H2304 [deceased donor, n = 488], H2307 [living donor, n = 284]) were pooled to further evaluate the efficacy and safety of everolimus with reduced tacrolimus (EVR + rTAC) versus standard tacrolimus (sTAC) regimen at month 24. Results: EVR + rTAC was comparable to sTAC for composite efficacy failure of treated biopsy-proven acute rejection, graft loss, or death (9.8% versus 10.8%; difference, −1.0%; 95% confidence interval, −5.4 to 3.4; P = 0.641) at month 24. EVR + rTAC was superior to sTAC for the mean change in estimated glomerular filtration rate (eGFR) from randomization to month 24 (−8.37 versus −13.40 mL/min/1.73 m 2 ; P = 0.001). A subanalysis of renal function by chronic kidney disease (CKD) stage at randomization showed significantly lower decline in eGFR from randomization to month 24 for patients with CKD stage 1/2 (eGFR ≥ 60 mL/min/1.73 m 2 ) in EVR + rTAC group versus sTAC (−12.82 versus −17.67 mL/min/1.73 m 2, P = 0.009). In patients transplanted for hepatocellular carcinoma (HCC) beyond Milan criteria, HCC recurrence was numerically lower although not statistically significant with EVR + rTAC versus sTAC group (5.9% [1 of 17] versus 23.1% [6 of 26], P = 0.215), while comparable in patients within Milan criteria (2.9% [3 of 102] versus 2.1% [2 of 96], P = 1.000), irrespective of pretransplant alpha-fetoprotein levels. Conclusions: EVR + rTAC versus sTAC showed comparable efficacy and safety with significantly better renal function, particularly in patients with normal/mildly decreased renal function (CKD stage 1/2) at randomization and a trend toward lower HCC recurrence in patients transplanted with HCC beyond Milan at month 24. Further long-term data would be required to confirm these results. Abstract : Supplemental Digital Content is available in the text.